Awareness on causes and transmission of malaria in rural Kolar of Southern India: a comparative study - Kumar S. J., Naresh; B. G., Ranganth (International Journal Of Community Medicine And Public Health, 2018)
Background: Malaria is a major public health problem in several parts of country. Malaria beliefs and practices are often related to culture, and can influence the effectiveness of control strategies. This study was undertaken to assess the awareness of malaria in rural areas of Kolar with varying endemicity. Methods: A cross sectional community based study was conducted. A sample of 207 Household respondents across the Kolar rural area were randomly selected and interviewed to collect information on awareness regarding Malaria. Two villages each were randomly selected from the two PHC areas in Mulbagal Taluk, Kolar District. PHC areas was taken based on annual parasite incidence more than 2 and less than 1 consistently in the past five years by using pre-tested structured proforma. Data analyzed by using epi info 2.5 version software. Results: It was observed that appropriate knowledge regarding malaria transmission from person to person is more in Devarayasamudra Primary Health Center area (69.2%) where API>2 compared to Nangli Primary Health Center area (26.2%) where API<1 and the knowledge regarding causes of malaria is also more in Devarayasamudra PHC area compared to Nangli area. Majority (87%) of the respondents got information about malaria from the health workers at Devarayasamudra PHC area. Conclusions: The Community knowledge on malaria, its transmission and its prevalence and control clearly depends on the endemicity of malaria. The communities studied under Devarayasamudra PHC area which is problematic for malaria had a better knowledge on malaria transmission and its prevention.